Signal variance-based collateral index in DSC perfusion: A novel method to assess leptomeningeal collateralization in acute ischaemic stroke. Issue 3 (March 2020) - Seiler, Alexander; Lauer, Arne; Deichmann, Ralf; Nöth, Ulrike; Herrmann, Eva; Berkefeld, Joachim; Singer, Oliver C; Pfeilschifter, Waltraud; Klein, Johannes C; Wagner, Marlies
As a determinant of the progression rate of the ischaemic process in acute large-vessel stroke, the degree of collateralization is a strong predictor of the clinical outcome after reperfusion therapy and may influence clinical decision-making. Therefore, the assessment of leptomeningeal collateralization is of major importance. The purpose of this study was to develop and evaluate a quantitative and observer-independent method for assessing leptomeningeal collateralization in acute large-vessel stroke based on signal variance characteristics in T2*-weighted dynamic susceptibility contrast (DSC) perfusion-weighted MR imaging (PWI). Voxels representing leptomeningeal collateral vessels were extracted according to the magnitude of signal variance in the PWI raw data time series in 55 patients with proximal large-artery occlusion and an intra-individual collateral vessel index (CVIPWI ) was calculated. CVIPWI correlated significantly with the initial ischaemic core volume (rho = −0.459, p = 0.0001) and the PWI/DWI mismatch ratio (rho = 0.494, p = 0.0001) as an indicator of the amount of salvageable tissue. Furthermore, CVIPWI was significantly negatively correlated with NIHSS and mRS at discharge (rho = −0.341, p = 0.015 and rho = −0.305, p = 0.023). In multivariate logistic regression, CVIPWI was an independent predictor of favourable functional outcome (mRS 0–2) (OR = 16.39, 95% CI 1.42–188.7, p = 0.025). CVIPWI provides useful rater-independent information on the leptomeningeal collateral supply in acute stroke.